2*x+3*y=12 log(6)^2*x*y+1=2*log(6*x)*y

Дано

$$y x \log^{2}{\left (6 \right )} + 1 = y 2 \log{\left (6 x \right )}$$
Численный ответ

x1 = 1.055210480304371 — 8.506141926989002e-30*i
y1 = 3.296526346463753 + 5.670761284647855e-30*i

x2 = 6.120553455735701
y2 = -0.08036897049046755

x3 = 1.055210480304371 + 8.947334021288308e-23*i
y3 = 3.296526346463753 — 5.964889347525526e-23*i

x4 = 1.055210480304371 — 4.927410485649459e-22*i
y4 = 3.296526346463753 + 3.284940323766306e-22*i

x5 = 6.120553455735701 — 3.09600845835857e-28*i
y5 = -0.08036897049046755 + 2.064005638905713e-28*i

x6 = 1.055210480304371
y6 = 3.296526346463753

x7 = 1.055210480304371 — 8.235515152744809e-39*i
y7 = 3.296526346463753 + 5.490343435163206e-39*i

x8 = 1.055210480304371 — 2.1435259350934e-31*i
y8 = 3.296526346463753 + 1.429017290081399e-31*i

x9 = 0.315640067496073
y9 = 3.789573288335951

x10 = 1.055210480304371 — 4.720267527155812e-33*i
y10 = 3.296526346463753 + 3.146845019538805e-33*i

x11 = 1.055210480304371 + 6.037933510504214e-30*i
y11 = 3.296526346463753 — 4.025289006956892e-30*i

x12 = 1.055210480304371 + 3.881082389461116e-27*i
y12 = 3.296526346463753 — 2.587388259640744e-27*i

x13 = 6.120553455735701 — 2.367886819696022e-39*i
y13 = -0.08036897049046755 + 1.578591096355809e-39*i

x14 = 1.055210480304371 — 3.305646993727991e-21*i
y14 = 3.296526346463753 + 2.203764662485327e-21*i

x15 = 1.055210480304371 + 1.486116369877347e-37*i
y15 = 3.296526346463753 — 9.907441905329593e-38*i

1 Звезда2 Звезды3 Звезды4 Звезды5 Звезд (Пока оценок нет)
Загрузка...